Uji Hipotesis Satu Sampel - Syah lestari, Selly; Tiapisah Samosir; Almira Amir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to examine and understand the one-sample hypothesis testing method as an important tool in data-based decision making in various fields, especially education and economics. The main problem raised was the lack of understanding of the procedure and application of appropriate one-sample hypothesis testing, which can affect the validity of research results and decision making. The methodology used is a literature study that examines various sources and journals related to statistics, including the basics of hypothesis testing, t tests. Data was collected through reviewing documents in the form of books and relevant scientific articles, then analyzed descriptively to identify procedural steps, types of errors that might occur, as well as the conditions for using certain statistical techniques according to the scale of the data. The research results show that an in-depth understanding of the steps of hypothesis testing, such as determining null and alternative hypotheses, significance levels, and interpreting statistical results, is very important to increase the accuracy and reliability of research. In addition, proper use of t tests can help researchers in effectively testing claims about population parameters. This research confirms that mastery of the one-sample hypothesis testing method is key in ensuring the validity of study results and supporting appropriate decision making in various research fields. Thus, this study makes an important contribution to improving the understanding and application of statistics in scientific research.